2006
DOI: 10.1121/1.2184268
|View full text |Cite
|
Sign up to set email alerts
|

Directional loudness in an anechoic sound field, head-related transfer functions, and binaural summation

Abstract: The effect of sound incidence angle on loudness was investigated using real sound sources positioned in an anechoic chamber. Eight normal-hearing listeners produced loudness matches between a frontal reference location and seven sources placed at other directions, both in the horizontal and median planes. Matches were obtained via a two-interval, adaptive forced-choice (2AFC) procedure for three center frequencies (0.4, 1, and 5 kHz) and two overall levels (45 and 65 dB SPL). The results showed that loudness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 20 publications
3
54
1
Order By: Relevance
“…Also Scharf (1969) indicated that binaural loudness summation of narrow-band signals was almost constant with level. This is further in line with recent data of Sivonen et al (2006) who also reported minimal influence from the stimulation level on binaural loudness summation. Consequently, even though the inter-aural level difference with BC stimulation was not controlled in the Stenfelt et al (2002) study, the influence from binaural loudness summation seem to be negligible and those data can be compared with the current study.…”
Section: Discussionsupporting
confidence: 81%
“…Also Scharf (1969) indicated that binaural loudness summation of narrow-band signals was almost constant with level. This is further in line with recent data of Sivonen et al (2006) who also reported minimal influence from the stimulation level on binaural loudness summation. Consequently, even though the inter-aural level difference with BC stimulation was not controlled in the Stenfelt et al (2002) study, the influence from binaural loudness summation seem to be negligible and those data can be compared with the current study.…”
Section: Discussionsupporting
confidence: 81%
“…However, it has been shown that directional loudness sensitivity (DLS) could be observed at 400 Hz [2], where there is little acoustic shadow of the head [4]. Moreover, a tendency for the measured DLS values to be slightly higher than model predictions based on the related pressure measurements was reported at 5000 Hz [5].…”
Section: Introductionmentioning
confidence: 99%
“…Signicant variations of loudness were observed when presenting bands of noise through loudspeakers that were located at various directions around a listener in an anechoic room [1,2]. As an example, a third-octave noise band centered at 5 kHz emitted by a lateral source (±90…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been explored on narrowband noises (Robinson and Whittle, 1960;Sivonen and Ellermeier, 2006) presented through loudspeakers located at several positions around the listener. The latter had to match the loudness of a test sound that was emitted from a given direction to that of a reference sound emitted from a reference direction.…”
Section: Introduction a Directional Loudnessmentioning
confidence: 99%
“…At-ear pressure modifications are included in binaural loudness models as sound pressure levels are needed at both ears in order to take binaural phenomena such as inhibition (the signal at one ear may inhibit the internal response to a signal at the other ear) into account (Moore and Glasberg, 2007;Moore et al, 2016). Sivonen and Ellermeier (2006) observed an effect of the source azimuth on loudness for narrow-band noises with a center frequency of 400 Hz, where the acoustic shadow of the listener's head is considered small (Moore, 2012). According to this, the modification of the at-ear sound pressure level, which is small for a distant source, couldn't fully account for the observed directional loudness.…”
Section: Introduction a Directional Loudnessmentioning
confidence: 99%